Risk Management Approach to Enhanced Construction Safety in Selangor - Kee , Yong Joo; Khalid, Zailawati; Sarpin, Norliana; Sallehuddin, Aina Mardia; Sabtu@Othman, Hilyati (Research in Management of Technology and Business, 2026)
The construction industry in Selangor keeps encountering safety problems. The Department of Occupational Safety and Health (DOSH) reports show that there are more injuries and deaths in construction. Most of the problems arise due to poor safety management, lack of training, weak leadership, using limitations technology, and acting on safety problems once they happen. The current objectives aimed to investigate the problems faced by the contractor towards implementing risk management in construction safety in Selangor, to identify the impact of implementation of implementation of risk management towards construction safety in Selangor, to suggest the improvement of risk management implementation in construction safety in Selangor. This study focuses on G7 contractors who registered with CIDB in Petaling district, Selangor. The total population G7 contractor in Petaling district is 1323, so the sampling size be 302 respondents. Out of this amount, 30 percent of the respondents or 91 contractors were chosen at random to take part in the project. The data analysis, in respect to the implementation of risk management approach, is done to the Statistical Package for Social Sciences, SPSS was discussed. It shows that risk management implementation involves risk identification and appropriate approaches such as safety training and improved communication provides a basis for improvement to construction safety performance and ensuring long-term sustainability of the construction industry in Selangor. This research identifies poor communication as the main problem in safety in the construction industry. The impact of failed safety is increasing projects expenses, while behavior-based safety is the suggestion to improvement. Focusing on safety through communication and behavior to enhance safety performance.